The effects of a supportive learning culture and rank on professional skepticism in information search - Grohnert, Therese; Gijselaers, Wim H.; Meuwissen, Roger H.G.; Trotman, Ken T. (Accounting, Organizations and Society, 2025)
Auditors at all ranks should be skeptical when searching for information throughout audits. However, we lever domain learning theory from educational psychology to posit that their skepticism unlikely develops evenly across ranks, but rather depends on a supportive learning culture, a construct from the management literature. To test that perceived learning culture moderates the association between auditor rank and skeptical information search, we use a laboratory study with 166 Dutch auditors at a Big 4 firm and follow-up interviews with seven top leaders of that firm. A more supportive perceived learning culture is associated with more skeptical information search, but only in audit managers and partners - not in associates and seniors. Interviewees attribute this pattern to values acquired over time through socialization, role expectations, knowledge development, and wider task characteristics.